Deconstructing the Criminal Justice System in Nepal: Toward a Victim-Centered Justice Paradigm within the Shadows of a Hybrid Legal System - Bimal Prasad Lamicchane; Kabita Dahal (Mimbar Keadilan, 2026)
Nepal’s criminal justice system, despite undergoing legislative reforms, remains entangled in a historical legacy rooted in hierarchical social structures and patriarchal values. This legal system, marked by minimal implementation of justice principles, has yet to realize a truly participatory and victim-centered model of justice. This study aims to evaluate the extent to which legal reforms in Nepal have ensured more equitable and victim-oriented justice, and how legal transformation within the criminal justice system can be actualized. Through a critical examination of Nepal’s legal history, constitutional texts, and legislative reform initiatives, this article assesses the dissonance between progressive legal theories and practical implementation. Employing a normative-juridical approach with an emphasis on critical legal analysis and a comparative-historical perspective, the study reveals that, despite legislative efforts to reduce inequality and discrimination, law enforcement practices continue to reflect structural disparities that neglect the needs of victims and reinforce state dominance in criminal proceedings. Accordingly, current reforms remain insufficient to achieve substantive change and necessitate an ideological transformation toward a legal paradigm that is more responsive and sensitive to victims’ rights.